Artikel Review : Studi Fitokimia Dan Farmakologi Tanaman Kelor (Moringa Oleifera Lam) - Ni’matul Fauziah; Miftahul Maulidiyah; Tiara Putri Hartanto; Silvia Nur Diana Putri; Annisya San Sabhira; Isna Wulan Mukarromah; Rizki Amalia Putri; Abdul Latif; Agustinus Alfred Seran; Ivan Charles S.Klau; Arista Wahyu Ningsih (The Journal General Health and Pharmaceutical Sciences Research, 2023)
The Moringa plant (Moringa oleifera L.) is a plant that has many properties in all parts of the plant. To find out the various properties, a phytochemical test is needed. Our phytochemical tests can determine the various chemical compounds formed and contained in plants, starting from chemical structure, biosynthesis, changes and metabolism, and bioactivity. This research aims to determine the classes of secondary metabolite compounds contained in the Moringa plant and their pharmacological activities based on the publication of scientific articles so that they can be a source of information in research and development of herbal medicines. The method used is literature study, the review process for this journal involves analysis of relevant articles, with a focus on empirical research conducted in the 2015-2023 time period. Article searches were carried out using the Google Scholar academic database. In the phytochemical test, it was found that Moringa contains alkaloids, saponins, flavonoids, terpenoids, steroids and tannins. These compounds are found in parts of the Moringa plant such as leaves, seeds, roots, protective skin, and stems. The Moringa plant also has pharmacological activities as antibacterial, anti-inflammatory, antioxidant, analgesic and anticancer.